Modified SCR (Selective Catalytic Reduction) catalyst as well as preparation method and application thereof

By adopting a modified structure in the SCR catalyst, including the first coating of components such as Mn/Cu-SSZ type first molecular sieve and cerium oxide, the problem of low NOx conversion at low temperatures is solved, and efficient NOx removal over a wider temperature range is achieved.

CN119733573AActive Publication Date: 2025-04-01SHANGHAI GOTEK CATALYST

Patent Information

Application Number
CN202411642240.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-01
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The low NOx conversion rate of existing SCR catalysts under low temperature conditions (<250°C), limiting their application effect in cold start or low load conditions, especially in cold areas.

Method used

Using a modified SCR catalyst, the catalyst comprises a straight-through ceramic honeycomb support and a first coating, which consists of a Mn/Cu-SSZ type first molecular sieve, cerium oxide, aluminum oxide and manganese oxide. The catalytic activity is improved in the low-temperature segment through this structure, and the denitrification performance of the medium- and high-temperature segment is ensured by partition coating.

Benefits of technology

The conversion rate of NOx is significantly improved in the low temperature section (150-250℃), while maintaining good denitrification performance in the medium- and high temperature section (250-500℃), ensuring the effectiveness of the catalyst under a wider operating temperature window.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733573A_ABST
    Figure CN119733573A_ABST
Patent Text Reader

Abstract

The invention provides an SCR (Selective Catalytic Reduction) catalyst as well as a preparation method and application thereof, the SCR catalyst comprises a straight-through ceramic honeycomb carrier and a first coating, and the first coating is coated on the surface of a pore channel of the straight-through ceramic honeycomb carrier; the first coating comprises a Mn / Cu-SSZ type first molecular sieve, cerium oxide, aluminum oxide and manganese oxide. The preparation method of the modified SCR catalyst provided by the invention is simple in process, the obtained catalyst still has excellent denitration performance at a low-temperature section of 150-200 DEG C after being subjected to hydrothermal aging at 800 DEG C, the denitration performance at a medium-high-temperature section of 250-500 DEG C is not lost, and good NOx conversion can be realized in a wider operation temperature window.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a modified SCR catalyst and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous improvement of environmental protection awareness and the increasingly stringent relevant regulations, how to effectively reduce NOx emissions in the exhaust of internal combustion engines, especially diesel engines, has become an important research topic. SCR technology is widely used in diesel vehicle exhaust aftertreatment systems due to its high NOx removal rate. However, existing SCR catalysts show low NOx conversion rates under low temperature conditions (<250°C), which limits their application effect under cold start or low load conditions. Especially in cold areas, the exhaust temperature of diesel engines is low during cold start, which causes the catalyst to be unable to quickly reach the operating temperature, affecting the NOx removal efficiency.

[0003] Manganese-based catalysts have high activity under low temperature conditions, especially in the temperature range of 150-200°C, and their NOx conversion rate is significantly higher than that of traditional vanadium-based and copper-based catalysts. This makes Mn-based catalysts perform particularly well under cold start and low load conditions of diesel engines. Traditional manganese-based catalysts use manganese oxide as the active component, accounting for more than 10% by mass. Although they have excellent denitrification performance at low temperatures, their performance at high temperatures is poor. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a modified SCR catalyst and a preparation method and use thereof, so as to solve the problems in the prior art.

[0005] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.

[0006] The invention provides a modified SCR catalyst, comprising a straight-through ceramic honeycomb carrier and a first coating, wherein the first coating is coated on the pore surface of the straight-through ceramic honeycomb carrier; the first coating comprises a Mn / Cu-SSZ type first molecular sieve, cerium oxide, aluminum oxide and manganese oxide.

[0007] Preferably, the straight-through ceramic honeycomb carrier is made of cordierite.

[0008] Preferably, the through-type ceramic honeycomb matrix has a pore density of 400 to 600 pores per square inch and a wall thickness h of 3 to 4 mils, where mil represents one thousandth of an inch.

[0009] Preferably, the slurry for forming the first coating layer comprises a Cu-SSZ first molecular sieve, a cerium ion-doped alumina material, a manganese salt, pseudo-boehmite, a pH adjuster and water.

[0010] Preferably, based on the solid content of the slurry forming the first coating, the content of the Cu-SSZ first molecular sieve is 50-81wt%, the content of the cerium ion doped alumina material is 15-48wt%, the content of pseudo-boehmite is 1.0-4.0wt%, and the content of manganese element is 0.5-4.0wt%.

[0011] For example, the content of the Cu-SSZ first molecular sieve is 50-60%, 60-70%, or 70-81%.

[0012] For example, the content of cerium ion-doped aluminum oxide material is 15.8-25%, 25-35%, 35-36.1%, 36.1-38.2%, 38.2-40%, 40-45%, 45-46.1%, and 46.1-48%.

[0013] For example, the Mn element content is 0.5-0.9%, 0.9-1.0%, 1.0-1.2%, 1.2-1.6%, 1.6-2.0%, 2.0-3.0%, 3.0-4.0%, and preferably 0.5-2.0%.

[0014] For example, the content of pseudo-boehmite is 1.0-2.0%, 2.0-3.0%, and 3.0-4.0%.

[0015] More preferably, the cerium ion-doped alumina material is formed by impregnating a cerium salt into alumina.

[0016] More preferably, in the cerium ion-doped aluminum oxide material, the molar ratio of cerium element to aluminum element is (0.01-0.05):1.

[0017] More preferably, the cerium salt is selected from acetate and / or nitrate.

[0018] More preferably, the manganese salt is selected from acetate and / or nitrate.

[0019] More preferably, the pH regulator is one or more selected from tartaric acid, nitric acid, hydrochloric acid and sulfuric acid, preferably tartaric acid. Tartaric acid not only acts as a pH regulator, but also as a chelating agent to improve the ability of aluminum oxide in the cerium ion-doped aluminum oxide material to adsorb manganese ions.

[0020] Preferably, the solid content of the slurry forming the first coating layer is 30-40 wt %.

[0021] Preferably, the pH of the slurry for forming the first coating layer is 4-5.

[0022] Preferably, the D50 of the slurry forming the first coating layer is 2-3 μm.

[0023] Preferably, the cerium oxide is CeO2.

[0024] Preferably, the aluminum oxide is Al2O3.

[0025] Preferably, the Mn / Cu-SSZ type first molecular sieve is Mn 2+ The first molecular sieve is obtained by ion exchange with Cu-SSZ type.

[0026] More preferably, the reaction temperature of the ion exchange is 40-60°C.

[0027] More preferably, the reaction time of the ion exchange method is 2 to 4 hours.

[0028] More preferably, the ion exchange medium is water.

[0029] More preferably, the Cu content in the Cu-SSZ type first molecular sieve is 1-2 wt %. The low Cu content is to reduce the difficulty of ion exchange of manganese ions, so that more manganese ions can be exchanged into the Cu-SSZ type first molecular sieve.

[0030] More preferably, the silicon-aluminum ratio of the Cu-SSZ type first molecular sieve is 20-22.

[0031] More preferably, the model of the Cu-SSZ type first molecular sieve is Cu-SSZ-13 type.

[0032] Preferably, a second coating is also included, and the slurry forming the second coating includes a Cu-SSZ type second molecular sieve, pseudo-boehmite and water. The second coating and the first coating are coated on the same straight-through ceramic honeycomb carrier in different zones. If they are coated on different straight-through ceramic honeycomb carriers and used in series during use, they also fall within the protection scope of this application.

[0033] More preferably, based on the solid content of the slurry forming the second coating layer, the content of the Cu-SSZ type second molecular sieve is 96-99wt%, and the content of the pseudo-boehmite is 1.0-4.0wt%.

[0034] More preferably, the solid content of the slurry for forming the second coating layer is 25-35 wt %.

[0035] More preferably, the D50 of the slurry forming the first coating layer is 2-3 μm.

[0036] More preferably, the Cu content in the Cu-SSZ type second molecular sieve is 2.5-3.5 wt%.

[0037] More preferably, the silicon-to-aluminum ratio of the Cu-SSZ type second molecular sieve is 20 to 22.

[0038] More preferably, the model of the Cu-SSZ type second molecular sieve is Cu-SSZ-13 type.

[0039] More preferably, the effective catalytic area ratio of the first coating layer to the second coating layer is (0.4-2.3): 1.

[0040] More preferably, the dry loading of the first coating is 80-100 g / L.

[0041] More preferably, the dry loading of the second coating is 80-100 g / L. The dry loading of the second coating is the ratio of the mass of the second coating to the volume of the straight-through ceramic honeycomb substrate.

[0042] The present invention also discloses a method for preparing the modified SCR catalyst as described above, comprising the following steps:

[0043] The cerium ion-doped alumina material is prepared into a slurry, which is referred to as slurry A;

[0044] The Mn / Cu-SSZ type first molecular sieve is prepared into a slurry, which is referred to as slurry B;

[0045] Mixing the slurry A and the slurry B to obtain a first coating slurry;

[0046] The first coating slurry is coated on the straight-through ceramic honeycomb carrier, and then dried and calcined.

[0047] Preferably, the pH of the slurry A is 4-5.

[0048] More preferably, the pH regulator of the slurry A is one or more selected from tartaric acid, nitric acid, hydrochloric acid and sulfuric acid.

[0049] Tartaric acid is preferred.

[0050] Preferably, the D50 of the slurry A is 2-3 μm.

[0051] Preferably, the D50 of the slurry B is 2-3 μm.

[0052] Preferably, the coating is carried out by vacuuming with feeding from below.

[0053] Preferably, the drying and calcining is to heat the mixture to 150-250°C at a heating rate of 5-10°C / min, keep the mixture warm for 0.5-1.5h, then continue to heat the mixture to 450-550°C at a heating rate of 5-10°C / min, keep the mixture warm for 1.5-2.5h, and then cool the mixture.

[0054] Preferably, after drying and calcining, the second coating slurry is coated on the straight-through ceramic honeycomb straight-through ceramic honeycomb carrier, followed by drying and calcining.

[0055] More preferably, the second coating slurry is obtained by mixing and grinding the Cu-SSZ type second molecular sieve, the pseudo-boehmite and the water.

[0056] The present invention also discloses the use of the modified SCR catalyst as described above for converting NOx in a low temperature window, wherein the low temperature window is 150-250°C.

[0057] Preferably, the modified SCR catalyst including the first coating layer and the second coating layer converts NOx in a wide temperature window, and the wide temperature window is 150-500°C.

[0058] The present invention also discloses a method for converting NOx using the modified SCR catalyst as described above. When in use, the reaction gas containing NOx flows along the pores of the modified SCR catalyst, first passes through the first coating area, and then flows to the second coating area.

[0059] The modified SCR catalyst disclosed in the present invention has a first coating layer in which the catalytically active components, Mn / Cu-SSZ type first molecular sieve and cerium oxide, greatly improve the catalytic activity of the catalyst in the low temperature section. The aluminum oxide in the cerium ion-doped aluminum oxide material is used to compete with the Mn / Cu-SSZ type first molecular sieve for adsorbing unexchanged manganese ions, and the manganese ions on the surface of the Mn / Cu-SSZ type first molecular sieve are adsorbed onto the aluminum oxide, thereby avoiding the conversion of manganese ions into oxides after a large amount of deposition on the surface of the Mn / Cu-SSZ type first molecular sieve, thereby blocking the molecular sieve pores and greatly reducing the catalytic activity. Furthermore, by reducing the Cu content in the Cu-SSZ type first molecular sieve and controlling the amount of manganese added in the first coating layer, more manganese ions are exchanged into the molecular sieve, thereby reducing the amount adsorbed on the surface of the Mn / Cu-SSZ type first molecular sieve and aluminum oxide, thereby preventing a large amount of adsorbed manganese ions from being converted into manganese oxide, thereby greatly reducing the denitration performance in the medium and high temperature sections. In addition, the denitration performance of the catalyst in the medium and high temperature sections is further ensured by adopting a partition coating method. By combining the above means, the first coating improves the denitration performance in the low temperature range of 150-250°C while ensuring the denitration performance in the medium and high temperature range of 250-500°C.

[0060] The present invention has the following beneficial effects:

[0061] The modified SCR catalyst preparation method provided by the present invention has a simple process, and improves the denitration activity of the catalyst in the low temperature range of 150-250°C after hydrothermal aging at 800°C, without losing the denitration performance in the medium and high temperature range of 250-500°C, and can achieve good NOx conversion in a wider operating temperature window. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 Shown is a schematic diagram of the structure of a portion of the pore wall in the SCR catalyst of the present invention.

[0063] Figure 2 Shown is a partial structural schematic diagram of the SCR catalyst of the present invention.

[0064] Figure 3 It shows the curve diagram of NOx conversion rate changing with temperature when the SCR catalysts in Examples 1 to 4 of the present invention are used.

[0065] Figure 4 It shows the curve of NOx conversion rate changing with temperature when the SCR catalysts in Examples 1, 5 to 8 of the present invention and Comparative Examples 1 to 2 are used.

[0066] Reference numerals:

[0067] 1 coating;

[0068] 11 first coating;

[0069] 12 second coating;

[0070] 3 straight-through ceramic honeycomb carrier. DETAILED DESCRIPTION

[0071] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0072] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0073] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0074] The raw materials used in the following examples are:

[0075] The silicon-aluminum ratio of the Cu-SSZ-13 type first molecular sieve and the Cu-SSZ-13 type second molecular sieve is 21;

[0076] The carriers are all cylindrical cordierite ceramic honeycomb carriers with a mesh number of 400, an end face diameter of 25 mm, and a length of 60 mm.

[0077] In the cerium ion-doped alumina material, the molar ratio of cerium to aluminum is 0.029:1.

[0078] The cerium ion-doped alumina material is formed by impregnating an alumina material with an aqueous solution of cerium nitrate hexahydrate.

[0079] The modified SCR catalyst prepared by the present invention is as follows Figure 1 As shown, it includes a straight-through ceramic honeycomb substrate 2 and a coating 1 coated on the surface of the straight-through ceramic honeycomb substrate; the coating 1 includes a first coating 11 and a second coating 12.

[0080] The modified SCR catalyst prepared by the present invention is as follows Figure 2 As shown, the reaction gas flows along the pores of the catalyst and contacts and reacts with the first coating and the second coating coated on the surface of the pores. The direction of the arrow indicates the flow direction of the reaction gas.

[0081] Example 1

[0082] This embodiment provides a specific modified SCR catalyst, and the preparation method is as follows:

[0083] 1. Preparation of the first coating slurry:

[0084] 15.14 g of cerium nitrate hexahydrate was dissolved in 17.26 g of deionized water to form an impregnation solution, which was added dropwise to 54 g of the second alumina, and then added to 113.6 g of deionized water. After adjusting the pH to 4.5 with tartaric acid, the slurry was ground to a D50 of 2.5 μm to obtain slurry A.

[0085] Take 84g of Cu-SSZ-13 first molecular sieve (Cu content is 1.5%), add it to 117.79g of deionized water, grind it to D50 of 2.5μm; add 8.21g of 50% manganese nitrate solution; continue stirring at 50°C for 3h to obtain slurry B;

[0086] Slurry B was poured into 168.47 g of slurry A, the pH was adjusted to 4.5 with tartaric acid, 4.2 g of pseudo-boehmite was added, the solid content was adjusted to 35%, and the mixture was mixed evenly to obtain the first coating slurry.

[0087] 2. Preparation of the second coating slurry:

[0088] Take 67.9g of Cu-SSZ-13 second molecular sieve (Cu content is 2.8%), add it to 90g of deionized water, and grind it to D50 of 2.5μm; add 2.1g of pseudo-boehmite, adjust the solid content to 35%, and mix well to obtain the second coating slurry.

[0089] 3. Coating

[0090] The first coating slurry was coated by vacuuming with feeding from below, and then dried and calcined. The first coating slurry was coated by vacuuming with feeding from below again, and after drying and calcining, a catalyst sample was obtained. The coating areas of the first coating and the second coating were the same, both being half of the overall catalyst, and the dry loading was 80 g / L.

[0091] The solid content of the first coating slurry in the catalyst includes 60% Cu-SSZ-13 first molecular sieve, 36.1% cerium ion doped alumina material, 0.9% Mn element, and 3% pseudo-boehmite. The solid content of the second coating slurry includes 97% Cu-SSZ-13 second molecular sieve and 3% pseudo-boehmite, as shown in Table 1.

[0092] Example 2

[0093] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of embodiment 1, except that:

[0094] The preparation method of the first coating slurry in step 1 is different.

[0095] Specifically, 15.14 g of cerium nitrate hexahydrate was dissolved in 17.26 g of deionized water to form an impregnation solution, which was then added dropwise to 54 g of the second alumina, and then added to 113.6 g of deionized water. After adjusting the pH to 4.5 with tartaric acid, the slurry was ground to a D50 of 2.5 μm to obtain slurry A.

[0096] 112 g of Cu-SSZ-13 first molecular sieve (Cu content of 1.5%) was added to 157.06 g of deionized water and ground to a D50 of 2.5 μm; 10.94 g of 50% manganese nitrate solution was added; the mixture was stirred at 50° C. for 3 h to obtain slurry B;

[0097] Slurry B was poured into 73.73 g of slurry A, the pH was adjusted to 4.5 with tartaric acid, 4.2 g of pseudo-boehmite was added, the solid content was adjusted to 35%, and the mixture was mixed evenly to obtain the first coating slurry.

[0098] The solid content of the first coating slurry in the catalyst includes 80% Cu-SSZ-13 first molecular sieve, 15.8% cerium ion doped alumina material, 1.2% Mn element, and 3% pseudo-boehmite. The solid content of the second coating slurry includes 97% Cu-SSZ-13 second molecular sieve and 3% pseudo-boehmite, as shown in Table 1.

[0099] Example 3

[0100] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of embodiment 1, except that:

[0101] The preparation method of the first coating slurry in step 1 is different.

[0102] Specifically, 22.71 g of cerium nitrate hexahydrate was dissolved in 25.89 g of deionized water to form an impregnation solution, which was then added dropwise to 81 g of the second alumina, and then added to 170.4 g of deionized water. After adjusting the pH to 4.5 with tartaric acid, the slurry was ground to a D50 of 2.5 μm to obtain slurry A.

[0103] 70 g of Cu-SSZ-13 first molecular sieve (Cu content of 1%) was added to 100.44 g of deionized water and ground to a D50 of 2.5 μm; 4.56 g of 50% manganese nitrate solution was added; the mixture was stirred at 50° C. for 3 h to obtain slurry B;

[0104] Slurry B was poured into 217 g of slurry A, the pH was adjusted to 4.5 with tartaric acid, 4.2 g of pseudo-boehmite was added, the solid content was adjusted to 35%, and the first coating slurry was obtained after mixing evenly.

[0105] The solid content of the first coating slurry in the catalyst includes 50% Cu-SSZ-13 first molecular sieve, 46.5% cerium ion doped alumina material, 0.5% Mn element, and 3% pseudo-boehmite. The solid content of the second coating slurry includes 97% Cu-SSZ-13 second molecular sieve and 3% pseudo-boehmite, as shown in Table 1.

[0106] Example 4

[0107] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of embodiment 1, except that:

[0108] The preparation method of the first coating slurry in step 1 is different.

[0109] Specifically, 15.14 g (0.029) of cerium nitrate hexahydrate was dissolved in 17.26 g of deionized water to form an impregnation solution, which was then added dropwise to 54 g (1 mol) of the second alumina, and then added to 113.6 g of deionized water. After adjusting the pH to 4.5 with tartaric acid, the slurry was ground to a D50 of 2.5 μm to obtain slurry A.

[0110] Take 84g of Cu-SSZ-13 first molecular sieve (Cu content is 1.5%), add it to 98.64g of deionized water, grind it to D50 of 2.5μm; add 27.36g of 50% manganese nitrate solution; continue stirring at 50°C for 3h to obtain slurry B;

[0111] Slurry B was poured into 158.67 g of slurry A, the pH was adjusted to 4.5 with tartaric acid, 4.2 g of pseudo-boehmite was added, the solid content was adjusted to 35%, and the mixture was mixed evenly to obtain the first coating slurry.

[0112] The solid content of the first coating slurry in the catalyst includes 60% Cu-SSZ-13 first molecular sieve, 34% cerium ion doped alumina material, 3% Mn element, and 3% pseudo-boehmite. The solid content of the second coating slurry includes 97% Cu-SSZ-13 second molecular sieve and 3% pseudo-boehmite, as shown in Table 1.

[0113] Example 5

[0114] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of Example 1, except that: in step 3, the first coating slurry is used to coat the entire pore of the straight-through ceramic honeycomb substrate, and the second coating slurry is not used, and the dry loading is 160 g / L. The remaining steps are the same as those of Example 1.

[0115] Example 6

[0116] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of Example 1, except that in step 3, the second coating slurry is used to coat the entire pores of the straight-through ceramic honeycomb carrier, and the first coating slurry is not used, and the dry loading is 160 g / L.

[0117] Preparation method of the second coating slurry: take 100g Cu-SSZ-13 second molecular sieve, add it to 120g deionized water, grind until D50 is 2.5μm, add 3g pseudo-boehmite, adjust the solid content to 40%, and mix well to obtain the second coating slurry.

[0118] The remaining steps are the same as those in Example 1.

[0119] Example 7

[0120] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of Example 1, except that 69% nitric acid is used instead of tartaric acid in step 1, and the remaining steps are the same as those of Example 1.

[0121] Example 8

[0122] This embodiment provides a specific modified SCR catalyst, and the preparation method is basically the same as that of embodiment 1, except that the Cu-SSZ-13 second molecular sieve is used to replace the Cu-SSZ-13 first molecular sieve. The rest of the preparation method is the same as that of embodiment 1.

[0123] Comparative Example 1

[0124] This comparative example is a comparative example of Example 1, except that in step 1, when preparing the first coating slurry, an equal amount of dry weight of slurry B is used to replace slurry A. The rest of the preparation method is the same as that of Example 1.

[0125] Comparative Example 2

[0126] This comparative example is a comparative example of Example 1, and the only difference is that the preparation method of the first coating slurry in step 1 is different.

[0127] Specifically, 15.14 g of cerium nitrate hexahydrate was dissolved in 17.26 g of deionized water to form an impregnation solution, which was then added dropwise to 54 g of the second alumina, and then added to 113.6 g of deionized water. After adjusting the pH to 4.5 with tartaric acid, the slurry was ground to a D50 of 2.5 μm to obtain slurry A.

[0128] Take 84g of Cu-SSZ-13 first molecular sieve (Cu content is 1.5%), add it to 80.40g of deionized water, grind it to D50 of 2.5μm; add 45.60g of 50% manganese nitrate solution; continue stirring at 50°C for 3h to obtain slurry B;

[0129] Slurry B was poured into 149.33 g of slurry A, the pH was adjusted to 4.5 with tartaric acid, 4.2 g of pseudo-boehmite was added, the solid content was adjusted to 35%, and the mixture was mixed evenly to obtain the first coating slurry.

[0130] The solid content of the first coating slurry in the catalyst includes 60% Cu-SSZ-13 first molecular sieve, 32% cerium ion doped alumina material, 5% Mn element, and 3% pseudo-boehmite, and the solid content of the second coating slurry includes 97% Cu-SSZ-13 second molecular sieve and 3% pseudo-boehmite.

[0131] Table 1

[0132]

[0133] The modified SCR catalysts prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were subjected to hydrothermal aging treatment at 800°C for 16 hours with a water vapor volume concentration of 10%, and then applied to a catalytic performance evaluation device to evaluate the NOx conversion performance of each catalyst in a wide temperature window.

[0134] The test conditions are as follows:

[0135] The gas components include: H2O (volume fraction 7%), O2 (volume fraction 10%), NO (400ppm), NH3 (400ppm), and the remaining components are nitrogen, with a space velocity of 60000h -1 , test temperature: 150-500℃, heating rate 10℃ / min, initial stable temperature 120℃.

[0136] The test method is as follows: use a blank straight-through ceramic honeycomb substrate, adjust the flowmeter parameters according to the above flue gas conditions and reach the preset values, record the concentration of each component at the reactor outlet after heating to 120°C and stabilizing, and ensure that the test conditions are stable; replace the blank straight-through ceramic honeycomb substrate with a test sample, set the heating rate after heating to 120°C and stabilizing, use a Fourier infrared flue gas analyzer to monitor the outlet NO concentration online, calculate the NO removal efficiency based on the inlet and outlet NO concentrations, and draw a relationship curve between temperature and NO removal efficiency, such as Figures 3-4 shown.

[0137] Depend on Figure 3 It can be seen that:

[0138] It can be seen from Examples 1 to 3 that as the content of the Cu-SSZ-13 first molecular sieve increases, the content of the cerium ion-doped alumina material and the Mn element decreases, and after the modified SCR catalyst is hydrothermally aged at 800°C, the denitrification performance in the low-temperature section improves, while the denitrification performance in the medium and high-temperature sections decreases; conversely, the denitrification performance in the low-temperature section decreases, while the denitrification performance in the medium and high-temperature sections improves.

[0139] It can be seen from Example 1 and Example 4 that when the content of the cerium ion-doped alumina material increases and the Mn element content decreases, the denitration performance of the modified SCR catalyst in the medium and high temperature sections decreases after hydrothermal aging at 800°C.

[0140] Depend on Figure 4 It can be seen that:

[0141] It can be seen from Examples 1 and 5 to 6 that when the modified SCR catalyst is prepared by coating with only the first coating slurry or the second coating slurry, the modified SCR catalyst cannot simultaneously have good denitrification performance in both the medium and high temperature sections and the low temperature sections after hydrothermal aging at 800°C.

[0142] It can be seen from Example 1 and Example 7 that if tartaric acid is not added, the denitration performance of the modified SCR catalyst in both the medium-high temperature section and the low temperature section is reduced after hydrothermal aging at 800°C.

[0143] It can be seen from Example 1 and Comparative Example 1 that if the cerium ion-doped alumina material is not added, the denitration performance of the modified SCR catalyst in the medium and high temperature sections is reduced after hydrothermal aging at 800°C, but the denitration performance in the low temperature section is greatly reduced.

[0144] It can be seen from Examples 1 and 8 that when the Cu content in the Cu-SSZ-13 first molecular sieve is increased to 2.8%, the denitration performance of the modified SCR catalyst is slightly improved in the low temperature section after hydrothermal aging at 800°C, but the denitration performance in the medium and high temperature sections is greatly reduced.

[0145] It can be seen from Example 1 and Comparative Example 2 that when the Mn element content is increased to 5%, the denitration performance of the modified SCR catalyst in the medium and high temperature sections decreases significantly after hydrothermal aging at 800°C.

[0146] The modified SCR catalyst of the present invention uses a Cu-SSZ type first molecular sieve doped with manganese ions and a low copper loading, so that ion exchange can be achieved under relatively mild conditions; at the same time, the alumina material doped with cerium ions adsorbs most of the unexchanged manganese ions under the promotion of a chelating agent, thereby avoiding the conversion of manganese ions into oxides after a large amount of deposition on the surface of the molecular sieve, which affects the denitration performance at high and low temperatures; in addition, a zoned coating method is adopted to further ensure the denitration performance of the catalyst in medium and high temperature sections.

[0147] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A modified SCR catalyst, characterized in that: It comprises a straight-through ceramic honeycomb substrate and a first coating, wherein the first coating is coated on the pore surface of the straight-through ceramic honeycomb substrate; The first coating layer includes a Mn / Cu-SSZ type first molecular sieve, cerium oxide, aluminum oxide and manganese oxide.

2. The modified SCR catalyst according to claim 1, characterized in that: The straight-through ceramic honeycomb carrier is made of cordierite; And / or, the pore density of the straight-through ceramic honeycomb carrier is 400-600 pores / square inch, and the wall thickness h is 3-4 mil; and / or, the slurry for forming the first coating includes a Cu-SSZ first molecular sieve, a cerium ion-doped alumina material, a manganese salt, pseudo-boehmite, a pH regulator and water; And / or, based on the solid content of the slurry forming the first coating, the content of the Cu-SSZ first molecular sieve is 50-81wt%, the content of the cerium ion-doped alumina material is 15-48wt%, the content of the pseudo-boehmite is 1.0-4.0wt%, and the content of the manganese element is 0.5-4.0wt%; and / or, the solid content of the slurry forming the first coating layer is 30-40wt%; and / or, the pH of the slurry forming the first coating layer is 4 to 5; and / or, the D50 of the slurry forming the first coating layer is 2-3 μm; And / or, the cerium oxide is CeO2; And / or, the aluminum oxide is Al2O3; And / or, the Mn / Cu-SSZ type first molecular sieve is Mn 2+ The first molecular sieve is obtained by ion exchange with Cu-SSZ type.

3. The modified SCR catalyst according to claim 2, characterized in that: The cerium ion-doped alumina material is formed by impregnating cerium salt into alumina; And / or, in the cerium ion-doped aluminum oxide material, the molar ratio of cerium element to aluminum element is (0.01-0.05):1; and / or, the manganese salt is selected from acetate and / or nitrate; And / or, the pH adjuster is one or more selected from tartaric acid, nitric acid, hydrochloric acid and sulfuric acid; And / or, the reaction temperature of the ion exchange is 40 to 60°C; And / or, the ion exchange medium is water; And / or, the Cu content in the Cu-SSZ type first molecular sieve is 1-2wt%; And / or, the silicon-to-aluminum ratio of the Cu-SSZ type first molecular sieve is 20 to 22; And / or, the model of the Cu-SSZ type first molecular sieve is Cu-SSZ-13 type.

4. The modified SCR catalyst according to claim 1, characterized in that The invention also comprises a second coating layer, wherein the slurry for forming the second coating layer comprises a Cu-SSZ type second molecular sieve, pseudo-boehmite and water.

5. The modified SCR catalyst according to claim 4, characterized in that: Based on the solid content of the slurry forming the second coating, the content of the Cu-SSZ type second molecular sieve is 96-99wt%, and the content of the pseudo-boehmite is 1.0-4.0wt%; and / or, the solid content of the slurry forming the second coating layer is 25 to 35 wt %; and / or, the D50 of the slurry forming the first coating layer is 2-3 μm; And / or, the Cu content in the Cu-SSZ type second molecular sieve is 2.5-3.5wt%; And / or, the silicon-aluminum ratio of the Cu-SSZ type second molecular sieve is 20 to 22; And / or, the model of the Cu-SSZ type second molecular sieve is Cu-SSZ-13 type; and / or, the effective catalytic area ratio of the first coating layer to the second coating layer is (0.4-2.3):1; and / or, the dry loading of the first coating is 80-100 g / L; And / or, the dry loading of the second coating is 80-100 g / L.

6. A method for preparing a modified SCR catalyst according to any one of claims 1 to 5, characterized in that: The steps include: The cerium ion-doped alumina material is prepared into a slurry, which is referred to as slurry A; The Mn / Cu-SSZ type first molecular sieve is prepared into a slurry, which is referred to as slurry B; Mixing the slurry A and the slurry B to obtain a first coating slurry; The first coating slurry is coated on the straight-through ceramic honeycomb carrier, and then dried and calcined.

7. The preparation method according to claim 6, characterized in that: Includes one or more of the following technical features: After drying and calcining, coating the second coating slurry on the straight-through ceramic honeycomb carrier, and then drying and calcining; The pH of the slurry A is 4 to 5; The coating adopts a bottom feeding vacuuming method; The drying and calcining process comprises heating the temperature to 150-250°C at a heating rate of 5-10°C / min, keeping the temperature for 0.5-1.5h, and then heating the temperature to 450-550°C at a heating rate of 5-10°C / min, keeping the temperature for 1.5-2.5h, and then cooling.

8. The preparation method according to claim 7, characterized in that: The second coating slurry is obtained by mixing and grinding the Cu-SSZ type second molecular sieve, the pseudo-boehmite and the water.

9. Use of the modified SCR catalyst according to any one of claims 1 to 5 for converting NOx into nitrogen at a low temperature window, wherein the low temperature window is 150 to 250°C.

10. A method for converting NOx using the modified SCR catalyst according to any one of claims 1 to 5, characterized in that: When in use, the reaction gas containing NOx flows along the pores of the modified SCR catalyst, first passes through the first coating area, and then flows to the second coating area.

Citation Information

Patent Citations

  • cooling OF A DYNAMOELECTRIC SYNCHRONOUS MACHINE.

    NO150500B

  • Impregnation-coating method for rapidly preparing Cu-SSZ-13 monolithic catalyst and application of monolithic catalyst

    CN109174171A

  • One-step preparation type transition metal modified molecular sieve monolithic catalyst and method

    CN109482226A

  • Honeycomb denitration catalyst for flue gas at 400°c-600°c and preparation method thereof

    US20170007990A1

  • Method for preparing molecular sieve-multielement oxide composite integrally extruded denitration catalyst

    US20190046962A1

Cited By

  • Modified SCR catalyst and preparation method therefor and use thereof

    WO2026103141A1